Sentinel lymph node diagnostic in prostate carcinoma: Part II: Biokinetics and dosimetry of 99mTc-Nanocolloid after intraprostatic injection - Wengenmair, H.; Kopp, J.; Vogt, H.; Wawroschek, F.; Gröber, S.; Dorn, R.; Heidenreich, P. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: To visualise the sentinel lymph nodes (SLNs) of the prostate we injected the radiotracer into the parenchyma of the prostate. The activity was deposited in liver, spleen, bone marrow, urinary bladder and regional lymphatic system. The aim of this work is to determine biokinetical data and to estimate radiation doses to the patient. Methods: The patients with prostate cancer received a sonographically controlled, transrectal administration of 99mTc-Nanocoll®, injected directly into both prostate lobes. In 10 randomly selected patients radionuclide distribution and its time course was determined via regions of interest (ROIs) over prostate, urinary bladder, liver, spleen and the lymph nodes. The uptake in the SLNs was estimated from gamma probe measurements at the surgically removed nodes. To compare tumour positive with tumour free lymph nodes according to SLN-uptake and SLNlocalisation we evaluated 108 lymph nodes out of 24 patients with tumour positive SLN. For calculating the effective dose according to ICRP 60 of the patients we used the MIRD-method and the Mirdose 3.1 software. Results: The average uptake of separate organs was: bladder content 24%, liver 25.5%, spleen 2%, sum of SLN 0.5%. An average of 9% of the applied activity remained in the prostate. The residual activity was mainly accumulated in bone marrow and blood. Occasionally a weak activity enrichment in intestinal tract and kidneys could be recognized. The effective dose to the patient was estimated to 7.6 μSv/MBq. The radioactivity uptake of the SLN varied in several orders of magnitude between 0.006% and 0.6%. The probability of SLN-metastasis was found to be independent from tracer uptake in the lymph node. The radioactivity uptake of the SLNs in distinct lymph node regions showed no significant differences. Conclusion: The radiotracer is transferred out of the prostate via blood flow, by direct transfer via the urethra into the bladder and by lymphatic transport. Injecting a total activity of 200 MBq leads to a mean effective dose of 1.5 mSv. It is not recommended to use the tracer uptake in lymph nodes as the only criterion to characterize SLNs.
Keywords: Sentinel lymph node; prostate cancer; nanocolloid; biodistribution; dosimetry